Reduction in EMI with BaTiO3 and Fe3O4 Thin Film grown by UBM Sputtering. (2017) - Ng, O.T.; Soh, C.B.; Liu, H.F.; Nguyen, X.S.; Ng, Edwin Y.C.
Abstract: The imaging and surveying ground areas with airborne sensors has important application for disaster monitoring, military application and rescue operation. The proposed solution seeks to explore a new approach in microwave shielding design through coating of high permittivity, hydrophilic oxide materials. To achieve this, multi-stacked metal oxides, Titanium Dioxide (TiO2 ), Barium Titanium Trioxide (BaTiO3 ) and Iron Ferrite (Fe) are deposited on the Sapphire ring and optical dome via Unbalanced Magnetron (UBM) sputtering. The complex permittivity (Ɛ' and Ɛ") and permeability (μ' and μ") of oxide-coated substrates are verified through measurement of their Scattering (S-) parameters (S11 and S21 ) via Vector Network Analyzer (VNA) between 300MHz to 18GHz regime by airline measurement technique for oxide sputtered on sapphire ring substrate. The optimal layers were sputtered on acrylic substrate as well as acrylic domes with arch reflectance result obtained using Pasco Kit measurement kit at 10.5GHz.